Improving Risk Management Maturity in Ultra Micro SOE Holding Companies - Susetyono, Eko; Priyarsono, Dominicus Savio; Sukmawati, Anggraini; Nurhayati, Popong (Pandawan, 2026)
The dynamics of global business are highly developed along with technological advances. This also happens to state-owned enterprises which are then merged into Ultra Micro (UMi) holding consisting of PT Bank Rakyat Indonesia Tbk (BRI), PT Pegadaian, and PT Permodalan Nasional Madani (PNM). For this reason, it is necessary to have the right strategy to improve risk management maturity in this UMi holding. The research used the Analytic Hierarchy Process (AHP) approach. This research methodology is descriptive-analytical, with the aim of describing and analysing the factors that influence risk management in ultra-micro holding, as well as identifying the best alternative strategies based on the comparison of relevant criteria. The questionnaire was distributed to 16 respondents consisting of experts (lecturers, Financial Services Authority (OJK), Bank Indonesia (BI), BRI, PT Pegadaian, and PNM. These findings indicate that based on the priority of the most impactful factor is Leadership, the actor is Holding BOD, the goal is Improved leadership quality and holding risk culture, while the alternative strategy Evaluate and improve the holding's integration plan (HR, operational and business) including risk management aspects. This finding shows that leadership is very important in the process of margers and acquisitions in order to improve risk management maturity. This research contributes to achieving Sustainable Development Goals (SDGs), particularly SDG 1 (No Poverty), SDG 8 (Decent Work and Economic Growth), and SDG 16 (Strong Institutions) by developing AHP-based strategies for improving risk management maturity in ultra-micro SOE holding companies, thereby enhancing their capacity to support inclusive economic development.